Umstrukturierung der Verschuldung und Wachstumsbedingungen: Griechenland und Argentinien im Vergleich - Musacchio, Andrés (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2012)
After the crisis of 2001/2002 Argentina was confronted with similar problems as Greece is nowadays. Argentina, however, recovered quickly. The article discusses which chances Greece has to follow a similar path of development and which are the obstacles for such a path.